Influence of weather conditions and the type of stack in the quality of Cupressus lusitanica Mill. Lumber, subjected to natural drying in Lages - SC Influência das condições meteorológicas e do método de empilhamento na qualidade da madeira serrada de Cupressus lusitanica Mill., submetida a secagem ao ar, em Lages - SC - Longo B.L.* (2014)
This study aimed to evaluate the wood quality of Cupressus lusitanica subjected to natural drying, according to three methods of stacking (tradicional, triangular and sqare). The material used in the study derived from experimental plantings 19 years old located in Campo Belo do Sul, SC, Brazil. The process of quality review boards began by determining the volume of parts and weigh the same. Regarding defects were used to NBR 12297 and ISO 1030, performing the analysis before and after drying. The air-drying was carried out in Lages and lasted 42 days, ending the process with approximately 17% humidity. All of the types of stack were significantly correlated with meteorological variables of temperature (minimum, average and maximum). Drying by the method of triangular stacking showed the highest rate for any defects evaluated, surpassing other methods only for bowing. Regarding warping, the defect occurred more frequently was bending. Among the cracks, the top was the most frequent.